Cerita etnis 5 negara serumpun - Hearty, Free, 1952- (Sumatra Barat, Indonesia: Women for Harmony Institute, 2013)
Short stories.
Koleksi Sumbangan :Abdul Ghafar Ibrahim (AGI)
In Indonesian, and some texts in Malay.